Are Graduates Working in Graduate Occupations? Insights from the Portuguese Labour Market - Suleman, F.; Figueiredo, M. C. T.; Guimarães, R. (Rethinking Graduate Employability in Context: Discourse, Policy and Practice, 2023)
Our study draws on the Portuguese linked employer-employee data (2007–2019) to examine the type of occupations assigned to young bachelor and master graduates. Empirical findings show positive signs but sound some alarms. Postgraduates are assigned to high-skilled jobs that could be done by bachelors, who are more likely to work in skilled non-manual or even elementary occupations. The wage gap across levels of education is increasing, thus devaluing the bachelor’s degree. We found that the wages of all young people declined due to the economic recession. The data show a gap between bachelor’s and master’s after the consolidation of the higher education reform. The expansion of higher education increased the supply of graduates, with the most marked consequences seen at the bachelor level.